(untitled) (Indian Journal of Arid Horticulture, 2025)
Kinnow is a major fruit crop in southwest Punjab, mainly canal irrigated, as the ground water is brackish. The inadequacy of the canal water warrants the use of the improved methods of irrigation including the drip system. Field experiments to evaluate drip and basin system versus basin were laid out in quadruplicate with a unit of five trees per replication and three levels of irrigation 35, 55, 75 per cent of pan evaporation. Drip system saved similar amount of water under all levels of irrigation allowing 142% net additional area irrigable on replacing basin irrigation. Drip irrigation increased the water content in the wetted zone, which increased the rooting density. Use of sodic water for over 2.5 years increased the soil pH and the electrical conductivity. The method could not become popular for lack of field verification of experimental results. Field verification of productive orchards drip irrigated from the beginning supported the experimental data. Thus the amount of water to be applied to kinnow through drip irrigation has been recommended. The recommendation is likely to increase the orchard area under drip system in the region.